2021
DOI: 10.1101/gr.271155.120
|View full text |Cite
|
Sign up to set email alerts
|

Local nucleosome dynamics and eviction following a double-strand break are reversible by NHEJ-mediated repair in the absence of DNA replication

Abstract: Although the molecular events required for the repair of double-strand breaks (DSB) have been well characterized, the role of epigenetic processes in the recognition and repair of DSBs has only been investigated at low resolution. We rapidly and synchronously induced a site-specific DSB in Saccharomyces cerevisiae upstream of the PHO5 locus, which has well-positioned nucleosomes. Utilizing MNase-seq epigenome mapping we interrogated the order of chromatin changes that occur immediately following a DSB by ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Assuming nucleosome spacing length of around 200 bp, this implies that the up to 2 kb accessible region from Fig. 5c lost up to ten nucleosomes 47 , 48 . We further uncovered a subpopulation of ATAC–seq reads spanning the target sites that significantly increased after Cas9 delivery ( P = 1.44 × 10 −18 , Student’s t -test) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Assuming nucleosome spacing length of around 200 bp, this implies that the up to 2 kb accessible region from Fig. 5c lost up to ten nucleosomes 47 , 48 . We further uncovered a subpopulation of ATAC–seq reads spanning the target sites that significantly increased after Cas9 delivery ( P = 1.44 × 10 −18 , Student’s t -test) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In vitro studies have shown that RecA molecules in the nucleoprotein filament possess ATPase activity that can influence (a) formation of a continuous filament during RecA loading on ssDNA 39 , (b) growth and shrinkage of the filament [40][41][42] , (c) release of the filament from heterologous pairing 35,43 , and (d) RecA turnover during strand invasion [42][43][44] . In vivo studies on double-strand break repair have made use of engineered endonuclease-based DSB-inducing systems (such as the I-SceI system) to make targeted breaks on the chromosome and track the associated dynamics [4][5][6]11,12,[45][46][47] . Using such a system in E. coli to study dynamics of long-distance homology search, imaging of RecA has revealed the presence of large assemblies of RecA, described as RecA filaments (or 'bundles'), that can even span the length of the cell 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the dense constitutive heterochromatin structure hinders an efficient DNA repair process and thus requires decompaction (Schieferstein and Thomä, 1998; Liu, 2015). Alteration of chromatin structure occurs during several DNA repair processes and often results from a change in nucleosome density (Waters et al ., 2015; Tripuraneni et al ., 2021; Chakraborty et al ., 2021). Few emerging models proposed that different chromatin remodeling events facilitate DNA repair, including nucleosome PTM erasure (Palomera-Sanchez et al ., 2010; Jeon et al ., 2020), nucleosome sliding and eviction (Dinant et al ., 2012; Matsumoto et al ., 2019; Nodelman and Bowman, 2021; Chakraborty et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%